Implementasi Uji Emisi Kendaraan Bermotor di Daerah Khusus Jakarta Dalam Pemenuhan Hak Masyarakat Untuk Hidup Sehat - Fakhri Naufal Aryoputro; Ridwan Ridwan (Jayapangus Press, 2025)
Air pollution in the Special Capital Region of Jakarta (DKJ) has reached an alarming level, significantly affecting public health. One of the main sources of air pollutants comes from motor vehicle emissions. The Jakarta Provincial Government has implemented an emission test policy to control air pollution and guarantee the citizens’ right to a healthy life, as mandated by Article 28H (1) of the 1945 Constitution. This study aims to analyze the implementation of the motor vehicle emission test policy in DKJ using Merilee S. Grindle’s policy implementation theory and T.H. Marshall’s concept of citizenship rights. The research employs a qualitative descriptive approach using secondary data from regulations, government reports, and academic publications. The results show that the implementation of the emission test policy has not been fully effective due to structural constraints, low public awareness, weak law enforcement, and limited testing infrastructure. From a citizenship rights perspective, Jakarta residents have not yet fully enjoyed their right to a healthy environment due to weak policy governance. Policy optimization can be achieved through institutional capacity building, multi-stakeholder collaboration, green transportation integration, and continuous public education.